2019
DOI: 10.5194/isprs-archives-xlii-3-w6-187-2019
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Approach for Kharif Rice Yield Prediction Integrating Multi-Temporal Vegetation Indices and Weather and Non-Weather Variables

Abstract: The development of kharif rice yield prediction models was attempted through Machine Learning approaches such as Artificial Neural Network and Random Forest for the 42 blocks covering 13,141 sq km upland rainfed area of Purulia and Bankura district, West Bengal. Models were developed integrating monthly NDVI with weather and non-weather variables at block-level for the period 2006 to 2015. The model correlation obtained was 0.702 with MSE 0.01. Though the weather variables vs NDVI models are quite satisfactory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…One of the reasons is that combining and averaging multiple base models to produce the final prediction improves accuracy compared to single model alone [37]. Our findings are in line with other studies conducted by Chandra et al, [38] and Wen et al, [39], which show that random forest can be used to predict the yield. Phan et al, [40] reported that a random forest model was better than a support vector machine model at predicting tea yield using MODIS-NDVI with R-squared between 0.67-0.71.…”
Section: Discussionsupporting
confidence: 90%
“…One of the reasons is that combining and averaging multiple base models to produce the final prediction improves accuracy compared to single model alone [37]. Our findings are in line with other studies conducted by Chandra et al, [38] and Wen et al, [39], which show that random forest can be used to predict the yield. Phan et al, [40] reported that a random forest model was better than a support vector machine model at predicting tea yield using MODIS-NDVI with R-squared between 0.67-0.71.…”
Section: Discussionsupporting
confidence: 90%
“…The analysis of the selected articles indicated that the studies differ with scale (ranging from field level to country level), ML algorithm (SVR, ANN, k-NN, GBR), platform (Sentinel, MODIS, LANDSAT), and crop (rice, wheat, sugarcane, arhar/tur). LANDSAT-8 satellite data with 30-meter resolution were effectively utilized for regional yield forecasting [69][70][71][72][73], followed by the images retrieved from MODIS [74][75][76]. Wolanin et al conducted wheat yield prediction in the Indo Gangetic Plains.…”
Section: Yield Predictionmentioning
confidence: 99%
“…The cloud-free image with a nominal 8-day revisit frequency was used to calculate eight VIs that covered the range of currently representative VIs in crop yield estimation (Newton et al 2018;Chandra et al 2019;, including SR, WDRVI, NDVI, SAVI, MSAVI, GNDVI, GCVI and EVI (Table 2). Finally, we used entire time-series of VIs to average into the yearly state.…”
Section: Vismentioning
confidence: 99%